Vacuum-ultraviolet absorption cross-sections of functionalized cyclic hydrocarbons: Six-membered rings. (October 2019) - Doner, Anna C.; Christianson, Matthew G.; Davis, Jacob C.; Koritzke, Alanna L.; Larsson, Alexander; Frandsen, Kelsey; Rotavera, Brandon
Abstract : Quantitative, high-resolution absorption spectra measured in the vacuum-ultraviolet for functionalized cyclic hydrocarbons, the majority of which for the first time. Absorption cross-sections calculated for intermediates relevant to combustion chemistry and atmospheric chemistry. Uncertainty analysis conducted. Extensive comparison with literature, including 1-butene and acetic acid. Abstract: Absorption cross-sections were measured in the vacuum ultraviolet (9.92–5.17 eV) using differential absorption spectroscopy for a series of six-membered hydrocarbon rings: cyclohexane, cyclohexene, 1, 3-cyclohexadiene, 1, 4-cyclohexadiene, benzene, tetrahydropyran, 3, 4-dihydro-2 H -pyran, 1, 4-dioxane, 1, 4-dioxene, cyclohexanol, cyclohexen-4-ol, cyclohexen-3-ol, cyclohexanone, cyclohexen-4-one, cyclohexen-3-one, 3, 4-epoxycyclohexene, and 4, 5-epoxycyclohexene. In addition, cross-sections for 1-butene and acetic acid were measured for comparison with the literature. Uncertainties were quantified in all cases by accounting for errors in gas-phase concentration, experimental repeatability, and signal-to-noise ratio as a function of photon energy. Convolving the sources of error using the root-sum-square method led to an upper limit of 5% uncertainty above the detection limit, which is largely attributable to chemical purity. The primary objective of the present work is to provide absolute cross-sections along with quantified uncertainty limits. The majority of the absorption spectra, which reflect electronic transitions such as σ → σ * and n → σ *, are reported for the first time and provide insight into fundamental chemical physics, such as vibrational band structure and Rydberg transitions. In addition, the absorption cross-sections enable quantitative isomer-resolved speciation measurements in combustion chemistry, photolysis calculations for laser spectroscopy and atmospheric chemistry, and spectral assignments in astrochemistry.